2022
DOI: 10.1093/jat/bkac017
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution Toward Designer Benzodiazepines in Drug-Facilitated Sexual Assault Cases

Abstract: Drug-facilitated sexual assault (DFSA) is a crime where the victim is unable to provide sexual consent due to an incapacitation resulting from alcohol or drug consumption. Due to the large number of substances possibly used in DFSA, including illicit, prescription and over-the-counter drugs, DFSA faces many toxicological challenges. Benzodiazepines (BZDs) are ideal candidates for DFSA, as they are active at low doses, have a fast onset of action, and can be easily administered orally. The last decade has seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…The log 1/c values predicted for several DBZDs (22 DBZDs in the study by Waters et al and 76 in the study by Catalaini et al) allowed the classification of molecules with predicted values higher than 8.0, considered to possess high GABA A R affinity. Interestingly, etizolam and flualprazolam, 2 of the most popular DBZDs 69 responsible for multiple fatalities, [70][71][72][73][74] showed predicted log 1/c values of 8.10 and 8.40, respectively. The top 10 predicted log 1/c values identified by Catalani et al showed putative biological activity levels up to 10 times higher (log 1/c = 9.40).…”
Section: Prediction Of Potencymentioning
confidence: 99%
“…The log 1/c values predicted for several DBZDs (22 DBZDs in the study by Waters et al and 76 in the study by Catalaini et al) allowed the classification of molecules with predicted values higher than 8.0, considered to possess high GABA A R affinity. Interestingly, etizolam and flualprazolam, 2 of the most popular DBZDs 69 responsible for multiple fatalities, [70][71][72][73][74] showed predicted log 1/c values of 8.10 and 8.40, respectively. The top 10 predicted log 1/c values identified by Catalani et al showed putative biological activity levels up to 10 times higher (log 1/c = 9.40).…”
Section: Prediction Of Potencymentioning
confidence: 99%
“…While there are a number of available designer benzodiazepines that are the active metabolite of a known benzodiazepine (desmethylflunitrazepam is the active metabolite of flunitrazepam; 3‐hydroxyphenazepam is the active metabolite of phenazepam), little is known about the active pharmacology of those compounds, but it is inferred that they are similar to the parent drugs (Katselou et al, 2017; Wilde et al, 2021). Nordiazepam, a desmethyl metabolite of diazepam, and cloniprazepam, a prodrug of clonazepam, have also been implicated in criminal cases (Orsolini et al, 2020; Pérez Orts et al, 2023; Yu et al, 2023; Wilde et al, 2021; Zawilska & Wojcieszak, 2019).…”
Section: Types Of Prodrugsmentioning
confidence: 99%
“…The effects of designer benzodiazepines that are active metabolites of other benzodiazepines are thought to be similar to those of the parent drugs, although the exact pharmacology may still be unknown and half‐lives are a challenge to estimate (Wilde et al, 2021). Designer benzodiazepines have been implicated in drug‐facilitated sexual assaults, including nordiazepam (desmethyldiazepam) an active metabolite of diazepam (Morgillo et al, 2023; Pérez Orts et al, 2023).…”
Section: Health and Public Safety Risksmentioning
confidence: 99%